MODELLING THE SEASONAL DYNAMICS OF HEAVY METAL POLLUTION OF WATER BODIES WITHIN A MINING AREA - Vasyl Popovych; Viktor Skrobala; Oleh Tyndyk; Mykhailo Petlovanyi; Kateryna Sai; Natalya Popovych; Roman Konanets; Bohdan Ilkiv (Rudarsko-geološko-naftni Zbornik)
Waste heaps from coal mines pollute the environment through spontaneous combustion of waste and contaminated wastewater leaking into underground and surface aquifers. Together with pollutants, a large concentration of heavy metals gets into the water. The object of this research is water bodies in the impact zone of the Chervonohrad mining district, a part of the Lviv-Volyn coal basin (Ukraine). Water chemical contamination level of anthropogenic reservoirs in the mining district was measured by indicators developed based on geochemical and hygienic environmental investigations. Methods of statistics of parameters of chemical pollution of water and soil; correlation analysis; data mining methods; assessment of similarity of ecotopes and grouping of chemical elements based on cluster analysis; multidimensional ordination of ecotopes in the space of geochemical indicators and graphical visualization based on Principle Component Analysis were used in the research. Chemical pollution of rivers and reservoirs in Male Polissia with heavy metals during the season is characterized by significant heterogeneity. The main reason of the deterioration of the ecological state of water bodies is related to the increase in the content of Mn, Ni, Cd, Pb compared to the maximum permissible concentration. The highest level of pollution during the entire monitoring season was observed in the water bodies at the foot of the Mezhyrichanska mine spoil tip near the city of Chervonohrad. Based on the correlation between the heavy metal content and the complex gradients of the aquatic environment, the following associations (groups) of chemical elements were identified: I - Cu, Pb, Co, Cd; II - Mn, Ni; III - Zn, Cr, Sr. The multidimensional ordination of water bodies on the axes of complex geochemical gradients of the environment reflects the seasonal dynamics of water pollution and its spatial features. The practical significance of the results obtained lies in the fact that forecasting dynamic trends, protection and restoration of ecosystem components are impossible without taking into account their relationships with environmental conditions, in particular, with the level of chemical pollution of water.